The The Effect of Pasteurization on the Quality and Shelf Life of Ready to Eat Southern Sour Curry - Yotmanee, Sanchai; Ploykhaw, Jerapat (PKRU SciTech Journal, 2022)
This research studied the pasteurization temperature (70, 80 and 90°C) and time (3, 5 and 7 min) on qualities of ready to eat Southern sour curry in laminated pouch. The results showed that the increasing of temperature and time resulted in the decreasing of L* (lightness) in curry products however their a* (redness) and b* (yellowness) were increased. The texture analysis of seabass in curry products showed that the increasing of pasteurization temperature resulted in the decreasing of their hardness, gumminess and chewiness (P<0.05). The analysis of chemical composition showed that lipid, protein, carbohydrate, fiber and ash in those products were significant different (P<005). However, there was no relation between pasteurization process and chemical composition. The microbiological evaluation showed that food pathogens were not found in curry products pasteurized at 80-90°C. Furthermore, the sensory evaluation of Southern sour curry in laminated pouch pasteurized at 80°C for 3 min showed that product was accepted by assessors with the mean scores was in the range of moderately like to very much like. For the evaluation of shelf life, pasteurized Southern sour curry in laminated pouch which kept at 4°C, was prolonged for 18 days, whereas the storage at room temperature was extended its shelf life for only 9 days. Therefore, this product could be supported for the commercialization.